Agrarian Change and Ethnic Politics: Restructuring of Hmong and Shan Labour and Agricultural Production in Northern Thailand. (4th August 2014) - Latt, Sai; Roth, Robin
<x xml:space="preserve">Abstract</x> Ethnic politics are an important, but under‐examined, dynamic in the restructuring of agrarian labour. This paper examines how the discursive construction of ethnic identity has facilitated the particular form of agrarian intensification and labour restructuring under way in the uplands of Thailand. Agricultural intensification, followed by the promotion of 'safe' and then 'organic' production, has relied upon the construction of Hmong farmers as environmentally destructive and in need of development, while Shan labour arriving from Burma are simultaneously constructed as 'illegal migrants' (as opposed to refugees), a social nuisance and hard workers, helping to make them into an available, willing and preferred labour force. We argue that the construction of ethnic identity in these instances enables the agricultural changes under way and, thus, the particularities of agricultural change cannot be understood without careful attention to ethnic politics.